Multiple model based fault localization for HVDC transmission systems: Robustness and real-world performance - Al Hage Ali, Ali; Piepenbreier, Bernhard; Buchstaller, Dominic; Engel, Markus (2016 IEEE/PES Transmission and Distribution Conference and Exposition, T and D 2016, 2016)
This paper discusses the robustness properties of a novel, model-based HVDC fault localization algorithm. The approach utilizes a bank of Kalman filters to rank the fit of a discrete set of line fault models to measured data. The best fitting model indicates the fault position and fault type. The robustness of the algorithm in the presence of disturbances and unmodeled dynamics is demonstrated using synthetic data from high fidelity simulations as well as field data from a real HVDC transmission system.
Keywords: fault localization; HVDC protection; Kalman filter; multi-terminal; multiple model